Leibniz : a contribution to the archaeology of power - Connelly, Stephen James (Edinburgh : Edinburgh University Press, 2021)
Drawing on thinkers as diverse as Aristotle, Aquinas, Duns Scotus, Grotius, Husserl and Deleuze, Connelly traces Leibniz's conceptualisation of power through its applications in his legal texts, revealing that Leibniz in fact reconceptualises power under a new name: the state space.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 26, 2021).
Keywords: Leibniz, Gottfried Wilhelm, -- Freiherr von, -- 1646-1716.; Power (Philosophy); Philosophy; History of philosophy, philosophical traditions